Single-Cell RNA-seq Analysis Reveals Cellular Functional Heterogeneity in Dermis Between Fibrotic and Regenerative Wound Healing Fates - Chen, Cao-Jie; Kajita, Hiroki; Takaya, Kento; Aramaki-Hattori, Noriko; Sakai, Shigeki; Asou, Toru; Kishi, Kazuo (Frontiers in Immunology, 2022)
Background: Fibrotic scars are common in both human and mouse skin wounds. However, wound-induced hair neogenesis in the murine wounding model often results in regenerative repair responses. Herein, we aimed to uncover cellular functional heterogeneity in dermis between fibrotic and regenerative wound healing fates. Methods: Expression matrix of single cell RNA sequencing (scRNA-seq) data of fibrotic and regenerative wound dermal cells was filtered, normalized, scaled, underwent principal components analysis, and further analyzed by UMAP for dimension reduction with Seurat package. Cells types were annotated and cell-cell communications were analyzed across cells. The core cell population myofibroblast was identified and biological functions of ligand and receptor genes between myofibroblast and macrophage were evaluated. Specific genes between fibrotic and regenerative myofibroblast and macrophage were identified. Temporal dynamics of myofibroblast and macrophage were reconstructed with Monocle tool. Results: Across dermal cells, there were six cell types including EN1-negative myofibroblast, EN1-positive myofibroblast, hematopoietic cell, macrophage, pericyte, and endothelial cell. Ligand and receptor genes between myofibroblasts and macrophages mainly modulated cell proliferation and migration, tube development and TGF-β pathway. Specific genes that were differentially expressed in fibrotic than regenerative myofibroblasts or macrophages were separately identified. Specific genes between fibrotic and regenerative myofibroblasts were involved in mRNA metabolic process and organelle organization. Specific genes between fibrotic and regenerative macrophages participated in regulating immunity and phagocytosis. We then observed the underlying evolution of myofibroblasts or macrophages. Conclusion: Collectively, our findings revealed that myofibroblasts and macrophages may alter the skin wound healing fate through modulating critical signaling pathways.